Analisis Pengaruh Independensi dan Profesionalisme Dewan Pengawas Syariah terhadap Kinerja Bank Perkreditan Rakyat Syariah di Jawa Tengah - Prasetyoningrum, Ari Kristin (STIE Widya Manggala, 2010)
Shari’a financial institution in Indonesia has shown fast development including one of them is Bank Perkreditan Rakyat Syari’ah (BPRS). Development of BPRS which is so fast brings concerns related to the purity of BPRS on shari’a principles so Dewan Pengawas Syari’ah (DPS) is formed. Realizing the importance of the role of DPS as a profession which can make public sure that service of BPRS followed by syari’a principles, so independence and professionalism of DPS is needed in their duties. This research examined the effect of economics and religious factor to the DPS independency so that effected the professionalism of DPS that would increase the performance of BPRS in Central Java. This research was quantitative that describes the level of eksplanative causality variables. The data obtained by using questionaire sent to all BPRS in Central Java. Measurement of variables using Likert scale, while an analysis tool used path analysis. Conclusion in this research is that economics and religious factor have a significant effect on the independence of DPS on BPRS in Central Java, DPS independency has a significant effect on professionalism of DPS with negative relation, DPS professionalism doesn’t significantly effect the Performance of BPRS and both of DPS independency and DPS professionalism doesn’t significantly effect the performance of BPRS.